Labour Supply and Informal Care Supply: The Impacts of Financial Support for Long-Term Elderly Care - Bruce Hollingsworth; Asako Ohinata; Matteo Picchio; Ian Walker (Institute of Labor Economics (IZA), 2017)
We investigate the impact of a policy reform, which introduced free formal personal care for all those aged 65 and above, on caregiving behaviour. Using a difference-in-differences estimator, we estimate that the free formal care reduced the probability of co-residential informal caregiving by 12.9%. Conditional on giving co-residential care, the mean reduction in the number of informal care hours is estimated to be 1.2 hours per week. The effect is particularly strong among older and less educated caregivers. In contrast to co-residential informal care, we find no change in extraresidential caregiving behaviour. We also observe that the average labour market participation and the number of hours worked increased in response to the policy introduction.
Keywords: C21; D14; I18; J14; 330; long-term elderly care; ageing; financial support; informal caregiving; difference-in-differences